Ill-Child Siblings: The Eternal Forgotten. Consequences Of This Experience In The Adulthood - Morales Méndez, Andrea Patricia (2022)
The objective of this research was to establish whether there are repercussions in adulthood after having experienced the palliative care disease process of a minor sibling during childhood or adolescence. The study follows a qualitative approach, a systematic design in grounded theory, and a typical case sample of four adults and two specialists in the subject. Both positive and negative effects were identified. Greater sensitivity to human pain, ease of empathy, and independence when making decisions were among the positive repercussions. The negative ones included fear of being vulnerable, difficulty relating to their parents, high-risk behaviors, among others.